2022
DOI: 10.3389/fimmu.2022.801639
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping of Human Papillomavirus-Positive Cervical Cancers Based on the Expression Profiles of 50 Genes

Abstract: BackgroundHuman papillomavirus-positive (HPV+) cervical cancers are highly heterogeneous in molecular and clinical features. However, the molecular classification of HPV+ cervical cancers remains insufficiently unexplored.MethodsBased on the expression profiles of 50 genes having the largest expression variations across the HPV+ cervical cancers in the TCGA-CESC dataset, we hierarchically clustered HPV+ cervical cancers to identify new subtypes. We further characterized molecular, phenotypic, and clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Relatedness of the DDR-associated processes and “heating-up” the immune TME has also been underscored by some researchers ( 42 , 46 48 ). As regards cell-type enrichment of the immune and stromal TME, our observations on early invasive CeCa are in agreement with the existence of immune-active and immune-suppressed phenotypes ( 49 51 ). However, intriguingly, cancer samples with an immune-active profile expressed relatively less well explored checkpoint markers, such as PDL2, BTN3A, TIGIT, and CD73; their dual stimulatory/inhibitory role in the immune response regulation attracts growing interest in view of their diagnostic/therapeutic potential.…”
Section: Discussionsupporting
confidence: 87%
“…Relatedness of the DDR-associated processes and “heating-up” the immune TME has also been underscored by some researchers ( 42 , 46 48 ). As regards cell-type enrichment of the immune and stromal TME, our observations on early invasive CeCa are in agreement with the existence of immune-active and immune-suppressed phenotypes ( 49 51 ). However, intriguingly, cancer samples with an immune-active profile expressed relatively less well explored checkpoint markers, such as PDL2, BTN3A, TIGIT, and CD73; their dual stimulatory/inhibitory role in the immune response regulation attracts growing interest in view of their diagnostic/therapeutic potential.…”
Section: Discussionsupporting
confidence: 87%
“…They revealed highly heterogenous molecular profiles across samples and identified three subtypes, i.e., the keratin-low squamous, keratin-high squamous and adenocarcinoma-rich subtype. Zhu et al identified two subtypes of HPV + CC based on the most varied 50 genes across CC samples 8 . Furthermore, an increasing number of studies have identified molecular units (including DNA, RNA, and proteins) as biomarkers for the diagnosis and treatment of CC [9][10][11] .…”
mentioning
confidence: 99%
“…Maud Kamal et al discovered the different integration signatures of HPV genome in cervical cancer that may imply prognostic significance (Kamal et al, 2021). With the 50 genes having the largest expression variation, Xiaojun Zhu et al demonstrated two molecular subgroups in cervical cancer and explored the heterogeneity, which provided novel targets for diagnosis and treatment (Zhu et al, 2022). Here we provided a novel classification approach to dissect the heterogeneity of cervical cancer from the immunological and metabolic perspectives.…”
Section: Discussionmentioning
confidence: 90%